(untitled) (Fiep Bulletin - online, 2014)
The Physical activities adopted are considered today a primary component for rehabilitation, independence, prevention of secondary illnesses and a better quality of life for persons that have any form of deficiency. Programs of Physical Activity on a regular and recreational basis may provide an individual who has a deficiency with a new out look on life. In this context, this article describes an experience of Physical Education in the Program of Motor Activities for those with deficiencies - (PROAMDE, in the Federal University of the Amazon with a group of participants that suffer the consequences of neurological problems such as; CVAs, Incomplete Medulla lesions, Cerebral Paralysis (CP) NS Cranial Encephalic traumatism (CET). This team was made up of 8 participants in the age group of 26-77 years old. Three being of the male gender and 5 females. The classes were taught twice a week from 2-3:30pm and included recreational games on an individual basis or in a group context. They were taught to march for (locomotion) re-educated of their muscles, the abilities in hadeling balls, and introducing them to diversion such as (Boccia, athletics, and table tennis or Ping Pong). They were also taught: socialization, hygiene and health, aspects of pedagogy, throwing exercises, walking, rolling, marching, and dislocation or the act of transfer, manipulation and others. The results were obtained from the assessments made from the semester evaluations and the accompaniment of the individuals diary. We obtained varied progressions from the participants in this group. They all obtained better, or more motor abilities, as well as the social and affectionate capabilities. Therefore we can affirm that the physical activities on a regular basis, bring about not only physical benefits, in the aspect of prevention of a reoccurrence of a CVA, but can also influence in a beneficiary way in their emotional well being. Thereby helping them to gain self-confidence, and autonomy.